20(R)-Ginsenoside Rg3 protects SH-SY5Y cells against apoptosis induced by oxygen and glucose deprivation/reperfusion. Issue 16 (15th August 2017) - He, Bo; Chen, Peng; Xie, Yu; Li, Shude; Zhang, Xiaochao; Yang, Renhua; Wang, Guihua; Shen, Zhiqiang; Wang, Hui
Graphical abstract: Abstract: As shown in our previous studies, 20( R )-ginsenoside Rg3 [20( R )-Rg3] exerts a neuroprotective effect on a rat model of transient focal cerebral ischemia, and the mechanism through which it decreases the mRNA expression of calpain I and caspase-3 has been delineated. However, researchers do not know whether 20( R )-Rg3 exhibits a neuroprotective effect following oxygen-glucose deprivation and reperfusion (OGD/R) injury in vitro . In the present study, 20( R )-Rg3 increased cell viability, decreased the LDH leakage rate, and inhibited the apoptosis rate in a concentration-dependent manner. In addition, 20( R )-Rg3 markedly decreased cleaved caspase-3 protein expression. Furthermore, 20( R )-Rg3 significantly decreased the Bax mRNA and protein levels and increased the levels of Bcl-2 mRNA and protein, subsequently decreasing the Bax/Bcl-2 protein ratio. Based on these findings, 20( R )-Rg3 exerts a neuroprotective effect against OGD/R-induced apoptosis.